Pengaruh Terpaan Media Sosial Twitter Terhadap Kepekaan Sosial Remaja di Kota Denpasar (Studi Pada utas “Twitter Please do Your Magic”) - Putri Utari, Nyoman Larashati; Purnawan, Ni Luh Ramaswati; Amanda Gelgel, Ni Made Ras (E-Jurnal Medium; Vol 2 No 2 (2021): Jurnal Ilmu Komunikasi Vol 2 No 2 Tahun 2021, 2021)
In this global era, social media has become part of people's daily lives, Twitter as an example. Twitter's popularity has increased since 2018, and a trend has emerged for the use of "Twitter, please do your magic”. The purpose of this study is to discover how Twitter as a social media affects the adolescent’s social sensitivity in Denpasar City. This study uses associative quantitative research methods using uses and effects as the theoretical base and involves up to 70 adolescent respondents. The data analyzed using simple linear regression. The result of this research indicate the level of exposure Twitter "Twitter please do your magic" on the adolescent’s social sensitivity in Denpasar City is in the medium range, but it is known to have a positive and significant influence value. Every increase detected in exposure of "Twitter please do your magic", the adolescent’s social sensitivity in Denpasar City will also increase.   Keywords : Twitter, Social Sensitivity, Social Media Exposure, Uses and Effects